Nicotinamide Increases the Physiological Performance and Initial Growth of Maize Plant - Tassila Aparecida do Nascimento de Araújo; Eduardo Pradi Vendruscolo; Flávio Ferreira da Silva Binotti; Edilson Costa; Sebastião Ferreira de Lima; Gabriela Rodrigues Sant’Ana; Fernanda Pacheco de Almeida Prado Bortolheiro (International Journal of Agronomy)
The objective of the work was to evaluate the effects of nicotinamide application via seed immersion on seed physiological quality and initial growth characteristics. Two experiments were carried out, in the laboratory (seed physiological potential) and another in a randomized block design, in a greenhouse (initial growth). Treatments consisted of immersion of seeds in six solutions with different concentrations of nicotinamide (0, 100, 200, 300, 400, and 500 mg·L−1). Characteristics related to primary root protrusion speed, average protrusion time, protrusion rate, and primary root length were evaluated under different temperature conditions (18°, 25°, and 35°C), and gas exchange, plant height, stalk diameter, number of leaves, aerial fresh weight, aerial dry weight, and root dry weight were evaluated. It was found that the use of nicotinamide, despite delaying the process of radicle protrusion, increases its development under stressful temperature conditions and results in an increase in gas exchange processes and gain in initial growth, mainly in the aerial part. Thus, it is concluded that the use of nicotinamide in maize seeds has the potential for use in stressful environments, as well as for obtaining greater initial growth, in which concentrations between 200 and 300 mg·L−1 are suitable for the crop.